Influence of Empowerment, Social Support, and Interpersonal Conflict on Employee Performance - Irfaniah Asmar; Afriyeni (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to examine the influence of empowerment, social support, and interpersonal conflict on employee performance at UIN Imam Bonjol Padang. The study used a quantitative approach with a survey design. Data were obtained by distributing questionnaires to 70 employees as respondents, then analyzed using multiple linear regression to test the influence of independent variables partially and simultaneously on the dependent variable. The test results show that empowerment has a positive and significant influence on performance, which indicates that increased empowerment contributes to improved employee performance. Social support also shows a positive and significant influence, where the existence of support from superiors and colleagues can strengthen motivation and create a conducive work environment. Conversely, interpersonal conflict is proven to have a negative and significant influence on performance, which means that increased conflict that is not managed well can reduce work effectiveness and productivity. On the other hand, interpersonal conflict has a negative and significant influence on performance, so that conflict that is not managed well has the potential to reduce employee productivity and work effectiveness. Overall, the three variables empowerment, social support, and interpersonal conflict simultaneously have a significant influence on employee performance at UIN Imam Bonjol Padang. Therefore, improving employee performance requires integrated efforts, such as strengthening empowerment, increasing social support in the workplace, and effectively managing interpersonal conflict to create a harmonious and productive work environment.